Perfection of the Cooperative Enterprises Legal Basics - Pečiuliauskas, Gintautas (Ekonomika, 2002)
An article deals with the legal basics of the cooperative enterprises, therein are presented suggestions how to improve them. It is taken into account the process of the cooperative enterprises validation in Lithuania while the reestablishment of the market intercourse, also there are presented the peculiarities of the legal provisions, which regulate the work of the cooperative enterprises, and revealed their influence to insufficient the development of enterprises activities. In addition, in the article are presented the research results of cooperative enterprises statute, according to cooperative enterprises statute there are given both a distribution of the cooperative enterprises by a set taxation and the distribution by value of member’s divvy. It is emphasised that those values are unjustifiably small, though a law sets them. Furthermore, there are given suggestions how the law cases could be improved. In this article there are also analysed and valuated conformity of the legal provisions to a universally accepted cooperative principles and presented an insufficient validity of provisions, which legalize and elaborate those principles.